A New Method to Calculate the Pure Component Parameters of Any Two-Parameter Equation of State. (12th October 2011) - Aljundi, Isam H.
Abstract : Reliable equations of state are very important in the design of refrigeration cycles, since thermodynamic properties can be calculated by simple differentiation. In this paper, a new method to calculate the parameters of any two-parameter equation of state is presented. The method is based on the use of Clapeyron equation and the experimental PVT data. This method was tested on a newly developed cubic equation of state and proved to be simple and fast. Results showed orders of magnitude enhancement in prediction of the saturated vapor pressure even near the critical region. The Percent Absolute Average Deviation (%AAD) was always less than 0.1 in the studied cases. It also showed that the parameters calculated using the original equation deviate strongly from the "experimental" values as the temperature decreases below the critical point. This method can be used to redefine the temperature dependences of these parameters and develop new mixing rules for the mixtures.